Role of facet in the competitive pathway of ethylene epoxidation - Nair, Aathira; Kenge, Nivedita; Joshi, Kavita (Surface Science, 2022)
Ethylene epoxide (EtO) is used as raw material for a broad range of products from pharmaceuticals and plastics to paints and adhesives. Although the reaction of ethylene interacting with preadsorbed oxygen on Ag surface is known for decades, the underlying mechanism of EtO formation is not completely understood. Successful investigation of oxametallacycle (OMC) intermediate common to selective as well as non-selective pathways has ensured at least 50% selectivity. The current study brings out the electronic signatures of distinct conformers of OMC stabilised on two different facets of Ag viz. (100) and (111). There are subtle differences between OMC conformers observed on these two facets with near-eclipsed on Ag(100) and near-staggered on Ag(111). A detailed analysis of Ag-O, C-O, C-C, and Ag-C interactions along with projected Density of States (pDOS) and projected Crystal Orbital Hamilton Population (pCOHP) imply towards ring closure on Ag(100) and hydrogen transfer on Ag(111). Finally, our understanding based on electronic and structural signatures are backed up by activation barriers computed through NEB calculations. Activation barrier for EtO is lower on (100) as compared to (111) facet. Thus, our study sheds light on how these differences between OMC affect the selectivity towards EtO.
Keywords: Ag(100); Ag(111); DFT; epoxidation; Ethylene Oxide (EtO); OMC